2011
DOI: 10.1179/1743676111y.0000000015
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic behaviour of explosively shattered alumina and silicon carbide targets

Abstract: The resistance offered by three ceramic materials of varying strength that have been subjected to explosive loading has been investigated by depth-of-penetration (DoP) testing. Each material was completely penetrated by a tungsten carbide-cored projectile and the residual penetration into a ductile aluminium alloy backing material was measured. The resulting ballistic performance of each damaged ceramic was found to be similar implying that the resistance offered to the projectile by the damaged ceramic is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…When material areal density was accounted for via differing ballistic efficiency calculations a strong indication of particle morphology influence on postimpact ceramic properties was apparent. These results were reinforced by a separate small series of plate-impact experiments, whose results indicated that powder morphology had a strong influence on the nature of compact collapse.which have shown that this comminuted materialon further compactionthen provides a residual resisting strength with respect to penetration [7,8,9]. The concept of ballistic strength discussed in this paper is essentially a measure of the ability of armour to resist penetration following an impact event.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…When material areal density was accounted for via differing ballistic efficiency calculations a strong indication of particle morphology influence on postimpact ceramic properties was apparent. These results were reinforced by a separate small series of plate-impact experiments, whose results indicated that powder morphology had a strong influence on the nature of compact collapse.which have shown that this comminuted materialon further compactionthen provides a residual resisting strength with respect to penetration [7,8,9]. The concept of ballistic strength discussed in this paper is essentially a measure of the ability of armour to resist penetration following an impact event.…”
mentioning
confidence: 65%
“…Building on this work, Nanda et al [7] employed an identical confinement rig to allow a variety of different ceramic materials to be explosively shattered before being subjected to depth-of-penetration testing. Experimental results indicated little difference in the subsequent ballistic mass efficiency (E m ; a comparison of the ballistic efficiency of the ceramic + backing to the backing alone [4]), despite substantially different initial ceramic strengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the validity of such an approach necessitates understanding of material hydrodynamic and constitutive equations-of-state for all elements involved. While a substantial body of research exists on the high-rate properties of munition [1] and armour-relevant [2,3] materials, there is less information available on the dynamic response and associated damage mechanisms in both tissues and potential analogues.…”
Section: Introductionmentioning
confidence: 98%
“…They do not provide efficient protection against multi-hit in a short space of time. After the first hit, armor system is expected to heavily damage and then any bullet would penetrate armor system which have already fractured [6]. Combining ceramic materials with a metal may provide better ballistic efficiency.…”
Section: Introductionmentioning
confidence: 99%